Szaleństwo jako norma. Antynomizm w działaniu żołnierzy, mafii, państw i korporacji - Sieradzan, Jacek (Humaniora. Czasopismo Internetowe, 2020)
The article is illustration of Victora Turner’s approach concerning liminality of phenomena both in social and ethical dimension. It shows liquid borders between state and self-defence social movements which from informal communitas transform into criminal organizations, and in time became states in state. The border between state and criminal organization can become liminal. Liminality of border between good and bad means not only that the same persons who in time of peace condem evil, during war glorify killing. It means also changing hierarchy of values in time of peace. As profitable and also good is regarded what serves smaller social group existing within the confines of bigger groups, for example criminal organization in a state, one state in the confines of community of states, or transnational corporation in world. In a country dominated by criminal organizations, crime is regarded as normalcy, and normalcy is treated as something curious and incomprehesible. Desire to improvement one’s social status at all costs is leading to criminalization of life and to living in permanent fear.